2017
DOI: 10.1002/smtd.201700192
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Perspectives in Microfluidics‐Based Single‐Cell Biosensing Techniques

Abstract: Single‐cell analyses of secretory proteins are essential to fully understand cellular functional heterogeneity and unravel the underlying mechanisms of intercellular signaling and interactions. Retrieving dynamic information of protein secretion at single‐cell resolution reflects the precise, real‐time functional states of individual cells in physiological processes. Such measurements remain very challenging in single‐cell analysis, which requires highly integrated systems capable of performing on‐chip single‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 327 publications
0
15
0
Order By: Relevance
“…This will result in concentrated molecular distribution in the vicinity of the sensor surface. In this regard, microfluidics technology offers a powerful tool to create a highly miniaturized environment with compartmentalization for the analysis . Nevertheless, the optical monitoring of an ultralow volume in cell culture conditions (i.e., 37 °C) introduces a significant evaporation problem.…”
Section: Introductionmentioning
confidence: 99%
“…This will result in concentrated molecular distribution in the vicinity of the sensor surface. In this regard, microfluidics technology offers a powerful tool to create a highly miniaturized environment with compartmentalization for the analysis . Nevertheless, the optical monitoring of an ultralow volume in cell culture conditions (i.e., 37 °C) introduces a significant evaporation problem.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices, tailored to approximately the size of individual cells with designed unique geometries and precise dimensions, confer inherent advantages over conventional technologies in single cell biology . The capability of integrating the multistep procedures of cell manipulation, lysis, and chemical analysis in a portable and enclosed device could reduce reagent consumption, decrease contamination risk, minimize lysate dilution, and increase assay sensitivity, which is critical for assaying low‐abundance biomolecules in single cells such as mRNA .…”
Section: Methodsmentioning
confidence: 99%
“…To a certain extent, the elasticity of polysaccharides can be controlled by the conformational transformation of the pyranose ring. [134,135] In particular, the transition will produce an atomic fingerprint in the force-stretch spectrum, whose characteristics depend on the energy conformation of the pyranose cyclic group and the type of glycosidic bond. [136] Through this method, it was found that the molecules contained in agarose and λcarrageenan produced the force spectrum characteristics of α-(1→4) D-glucan when the AFM is stretched, and thus AFM can be used to identify the components of polysaccharide mixtures at the single-molecule level.…”
Section: Characterization Of Proteins and Carbohydrate Molecules On The Surfaces Of Living Cellsmentioning
confidence: 99%